SURVEI MAWAS DIRI DI POSYANDU ANGGREK 2 KELURAHAN BELO KOTA KUPANG - Conrad Folamauk; Alexandro Bermistlaf Seong; Dwie Kurnian; Tiara Ramadani (Jurnal Media Tropika, 2023)
National health development focuses on preventive and promotive efforts to increase awareness, willingness, and the ability to live healthily for everyone. The activities carried out at the Anggrek 2 Belo Sikumana Posyandu used the stages of work, namely: Conducting an anamnesis with several residents in the area and providing KIE to residents in the area. Conduct a through evaluation of processes and performance as well as reporting of all activity results, including temporary conclusions and suggestions for further activities. From the results of the Self-Introspective Survey, it was found that there was still a lack of public knowledge and information about the health problems surrounding them. It was also found that the information they obtained regarding a health problem was obtained if someone in their family experienced it, direct information from health workers and the public media around them. There is still a lack of information that they know about health problems such as stunting, information on prenatal care, childbirth, and information on complete basic immunization. From the survey results it was also found that there was still a lack of community behavior in maintaining health such as exercising and washing hands due to the bathroom being outside the home. Education related to family and community health problems needs to be carried out so that public health knowledge increases and a better understanding of existing health problems.